Coatable Photomobile Polymer Films Using Spring‐Like Photochromic Compounds. Issue 8 (26th February 2018) - Kondo, Mizuho; Makino, Kotaro; Miyake, Kazutoshi; Matsuo, Yoshiaki; Fukae, Ryohei; Kawatsuki, Nobuhiro
Abstract: Photoinduced macroscopic deformation behavior of crosslinked liquid‐crystalline polymer is induced in crosslinked N ‐benzylideneaniline polymer films. The film is prepared by in situ polymer reaction using polymethacrylate‐containing phenylaldehyde side chains and o ‐tolidine crosslinker. The film exhibits macroscopic bending upon exposure to UV light and then immediately reverts to the initial shape when the light is turned off. The bending behavior is strongly affected by the fabrication conditions; the changes in the macroscopic shape and photomechanical properties in response to UV light for the film prepared from a mixture solution are small, while those for the film prepared by top coating the crosslinker solution onto the prepolymer substrate are large. Abstract : Easily fabricated photomobile liquid‐crystalline polymer films are developed using N ‐benzylideneaniline as a photoresponsive mesogenic crosslinker. Upon exposure to UV light, the film exhibits macroscopic bending and then spontaneously reverts to the initial shape when the light is turned off. The bending behavior is affected by the surface composition of the film determined by the preparation process.